An analytical study of achievement test questions and the extent of measuring the targeted competencies in the Arabic language subject at the intermediate stage - Alhazmi, Khalid Ahmed (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to analyze the achievement test questions, and to identify the extent to which they measure the target competencies in the Arabic language for the intermediate stage. Based on the table of specifications and relative weights of the achievement test for the first semester of the year 1443 AH issued by the Arabic Language Department in the Department of Jeddah Education and based on the competencies targeted in the language course for the intermediate stage in the first semester, The results showed that the questions that were asked to measure the competencies of the reading comprehension component came at a low level (41%), and the paragraphs measuring the competencies of the grammatical function component came at a level available at a medium degree and a percentage of (48%), as well as the questions that measure the competencies of the language category component at a rate of (37%) and at a low level, and the questions that measure the competencies of the language component The linguistic approach has a moderately available level of availability (41%), and the questions that measure the competencies of the spelling component come at a moderately available level and (51%), and the questions that measure the competencies of the written drawing component are (48%) and a level is available to a medium degree. The results also showed that the extent to which the target competencies were measured at the grade level were as follows: the third grade was average, the level of availability was average at (44.05%), and the level of availability of questions that measured the target competencies in the first grade came in the second place with a rate of (44.4%), and the level was medium. The questions of measuring the target competencies in the second intermediate grade provide the lowest percentage (41.2%) and an average average in the last rank.
Keywords: Achievement test; competencies; Arabic language course; intermediate stage; Saudi Arabia